THE MUSICAL PORTRAYAL OF CHARACTERS IN THE LYRICAL GENRE - Luminița STOIAN (Studia Universitatis Babeş-Bolyai. Musica, 2018)
This study aims to highlight the methods of musical expressiveness used by the composer Teodor Zgureanu when portraying the characters in his opera, ”Decebalus”. He depicts his characters by resorting to a certain vocal method. Mainly, each of the characters has their own, reserved space. Hence, each of them is offered, at least, one solo number (an aria or monologue). Zgureanu tries to find the most efficient formulas for establishing, in terms of sound, the dialectic of moods and personality of the characters.